Bidirectional Dysregulation of AMPA Receptor-Mediated Synaptic Transmission and Plasticity in Brain Disorders - Zhang, Hongyu; Bramham, Clive R. (Frontiers in Synaptic Neuroscience, 2020)
AMPA receptors (AMPARs) are glutamate-gated ion channels that mediate the majority of fast excitatory synaptic transmission throughout the brain. Changes in the properties and postsynaptic abundance of AMPARs are pivotal mechanisms in synaptic plasticity, such as long-term potentiation (LTP) and long-term depression (LTD) of synaptic transmission. A wide range of neurodegenerative, neurodevelopmental and neuropsychiatric disorders, despite their extremely diverse etiology, pathogenesis and symptoms, exhibit brain region-specific and AMPAR subunit-specific aberrations in synaptic transmission or plasticity. These include abnormally enhanced or reduced AMPAR-mediated synaptic transmission or plasticity. Bidirectional reversal of these changes by targeting AMPAR subunits or trafficking ameliorates drug-seeking behavior, chronic pain, epileptic seizures, or cognitive deficits. This indicates that bidirectional dysregulation of AMPAR-mediated synaptic transmission or plasticity may contribute to the expression of many brain disorders and therefore serve as a therapeutic target. Here, we provide a synopsis of bidirectional AMPAR dysregulation in animal models of brain disorders and review the preclinical evidence on the therapeutic targeting of AMPARs.